2018
DOI: 10.1007/s11626-018-0234-x
|View full text |Cite
|
Sign up to set email alerts
|

Thalidomide induces apoptosis during early mesodermal differentiation of human induced pluripotent stem cells

Abstract: Thalidomide was once administered to pregnant women as a mild sedative; however, it was subsequently shown to be strongly teratogenic. Recently, there has been renewed interest in thalidomide because of its curative effects against intractable diseases. However, the teratogenicity of thalidomide is manifested in various ways and is still not fully understood. In the present study, we evaluated the effects of thalidomide on early mesodermal differentiation by examining the differentiation of human induced pluri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…As thalidomide has multiple effects on body homeostasis, the specific mechanisms remain debated. It has been suggested that thalidomide disrupts the early mesodermal differentiation by damaging undifferentiated cells (Tachikawa et al 2018) as well as resulting in anti-angiogenesis, evasion of apoptosis and inhibition of pro-inflammatory innate responses (Paravar and Lee 2008;Hideshima et al 2000;Du et al 2005). Furthermore, thalidomide can bind as an antagonist to the androgen receptor (AR) (Capitosti et al 2004) and hence inhibit different androgens like testosterone which have a pivotal impact during development of male secondary sex characteristics and reproductive tissues.…”
Section: Thalidomidementioning
confidence: 99%
“…As thalidomide has multiple effects on body homeostasis, the specific mechanisms remain debated. It has been suggested that thalidomide disrupts the early mesodermal differentiation by damaging undifferentiated cells (Tachikawa et al 2018) as well as resulting in anti-angiogenesis, evasion of apoptosis and inhibition of pro-inflammatory innate responses (Paravar and Lee 2008;Hideshima et al 2000;Du et al 2005). Furthermore, thalidomide can bind as an antagonist to the androgen receptor (AR) (Capitosti et al 2004) and hence inhibit different androgens like testosterone which have a pivotal impact during development of male secondary sex characteristics and reproductive tissues.…”
Section: Thalidomidementioning
confidence: 99%
“…Human pluripotent stem cells have proven useful in investigating the teratogenicity of thalidomide in vitro. Studies on the effect of thalidomide on human pluripotent stem cells (hPSCs) characterized cytotoxicity in undifferentiated hPSCs 19,20 and hPSC-derived mesoderm 21 and functional effects on hPSC-derived mesendoderm 22 and cardiac mesoderm 20 at concentrations above 100 µM. However, these studies demonstrated effects of thalidomide on PSCs or PSC-derived mesoderm in vitro at concentrations >5-fold in excess of the thalidomide clinical Cmax 7 , which raises concern regarding the relevance of these effects to thalidomide teratogenicity.…”
mentioning
confidence: 99%